REPRESENTASI EMOSIONAL DALAM CUITAN X KOMUNITAS SEDIH-SEDIH: KAJIAN PSIKOLINGUISTIK - Alfatika Alya Ananda; Nabila Dea Nurcahyani; Sundawati Tisnasari (Jurnal Bastra (Bahasa dan Sastra), 2025)
This journal reviews "Emotion Representation in Tweets of X Sad-sad Community: A Psycholinguistic Study". The purpose of this study is to investigate the feelings expressed in the sad-sad community's Twitter tweets, which include both positive and negative values in their online social interactions. The topics covered and the setting of each article will determine this. By describing the data that already exists, a qualitative approach is employed. Techniques for gathering data were done in two steps: recording and listening. This study's tools included notebooks, cell phones, and laptops. The Miles, Huberman, and Saldana model was employed for data analysis. The findings demonstrated that researchers used the sad-sad community's Twitter tweets, which reflected all of the emotions that people experienced. The sad-sad community's Twitter tweets express a range of emotions, including hurt, sadness, disappointment, exhaustion, rage, and a sense of being undervalued. It can be seen that the interaction of X users with sad-sad tweets is a natural reaction of the body to something encountered.